Respuestas

  • Usuario de Brainly
2013-12-18T23:05:07+01:00
(3x^2+2+6x^2)2/3=5
(9x^2+2)2/3=5
9x^2*2/3 +2*2/3=5
6x^2+4/3=5
6x^2 =5-4/3
6x^2=(15-4)/3
6x^2=9/3
6x^2=11/3
x^2 =(11/3)/6
x^2=11/18
x=+raiz de11/18  o  x=- raiz de 11/18
2013-12-19T00:09:31+01:00
(3*x^2+2+6*x^2)*(2)/3=5

((3*x^2+2+6*x^2)*2)/3=5
common denominator is 3

(3*(3*x^2+2+6*x^2)*2)/3=3*5

(3*(3*x^2+2+6*x^2)*2)/3=3*5

(3*x^2+2+6*x^2)*2=3*5

(9*x^2+2)*2=3*5

(9*x^2+2)*2=15
distributing 2 through parentheses

9*x^2*2+2*2=15

18*x^2+2*2=15

18*x^2+4=15
subtract 4

18*x^2=15-4

18*x^2=11

x^2=11/18

x_1,2=±√11/18

x_1,2=±0.782